2013
DOI: 10.5172/jamh.2013.12.1.22
|View full text |Cite
|
Sign up to set email alerts
|

The views of lesbian, gay and bisexual youth regarding computerised self-help for depression: An exploratory study

Abstract: Abstract:Background: Lesbian, gay or bisexual (LGB) youth with depression are often isolated and face

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 26 publications
3
61
0
1
Order By: Relevance
“…This corroborates with past research in this area, which has found that no existing computerized cognitive behavioral therapy (cCBT) programs address challenges specific to lesbians and gay men [16]. It also reinforces broader work that demonstrates a shortage of mental health care that caters to the needs of same-sex attracted populations [16,28,31]. This is despite a comprehensive and growing body of research that shows that therapy modes that fail to do so can alienate lesbians and gay men and lead to diminished therapeutic outcomes [27,29-31,34].…”
Section: Discussionsupporting
confidence: 90%
“…This corroborates with past research in this area, which has found that no existing computerized cognitive behavioral therapy (cCBT) programs address challenges specific to lesbians and gay men [16]. It also reinforces broader work that demonstrates a shortage of mental health care that caters to the needs of same-sex attracted populations [16,28,31]. This is despite a comprehensive and growing body of research that shows that therapy modes that fail to do so can alienate lesbians and gay men and lead to diminished therapeutic outcomes [27,29-31,34].…”
Section: Discussionsupporting
confidence: 90%
“…Table 1 presents details of the included studies (k = 33). Sixteen studies were aimed at computerized treatments, of which nine were unguided computerized treatments (four computer-based and five internet-based) [30][31][32][33][34][35][36][37][38] and seven studies were guided computerized treatments (one computer-based and six internet-bases) [39][40][41][42][43][44][45], two studies at blended treatment [46,47], two studies compared unguided computerized, blended-and face-to-face treatment to no treatment [48,49], and eight studies were aimed at self-help internet-based games [50][51][52][53][54][55][56][57]. Furthermore, two studies that were focused on the use of an online monitoring tool aimed at registering and monitoring treatment progression [58,59] and three studies were aimed at characteristics of online interventions or studied the preferred modes of help seeking [60][61][62].…”
Section: Data Extractionmentioning
confidence: 99%
“…Sixteen studies were mainly focused on the feasibility, usability, and acceptability of computerized and blended interventions. The study designs were mixed and they contained qualitative studies with focus groups of patients, healthy adolescents or mental health professionals (k = 6) [41,53,54,56,58,59], randomized controlled trials (k = 3) [43,47,48], pre-post designs without control group (k = 5) [31,46,50,51,55], and cross-sectional studies (k = 2) [32,37]. Three studies were mainly focused on the preferences of patients regarding treatment modalities [32,60,62].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, experiencing mistreatment and stress results in LGBT+ individuals frequently internalizing the negativity associated with anti-LGBT+ messages. This in turn can lead to self-loathing and a range of unhelpful cognitions, which are then thought to place LGBT+ young people at greater risk of mental health problems, such as depression [6]. Moreover, it is not unusual for LGBT+ young people to face the challenge of navigating multiple stigmas related to difference, such as being LGBT+ and having mental health problems [7] or being an ethnic minority and LGBT+ [8].…”
Section: Introductionmentioning
confidence: 99%